Visual Impairment in the Virtual Workplace: Exploration, Experience, and Interpretation. (July 2021) - Makkawy, Amin; Long, Shawn
Introduction: This study utilizes interpretive phenomenology to understand the experiences of people with visual impairments in the virtual workplace. As virtual work is becoming increasingly common, this investigation is timely for employment research that is especially relevant to people who are visually impaired.Methods: Using an interpretive phenomenological approach, individuals who have experienced working in the virtual workplace filled out an in-depth online questionnaire. The resulting qualitative data were analyzed and interpreted via Applied Thematic Data Analysis (ATDA). ATDA was used to transform the raw qualitative data into themes regarding the essence of the experience of being a visually impaired employee in the virtual workplace.Results: Based on the phenomenological data, three primary themes emerged: defined by blindness, technology as the catalyst of inequality, and ingenuity as efficacy.Discussion: Using co-cultural theory, in-depth interpretations of the data were conducted. Key to these interpretations were the technological and communicative structures that mute the voice of the virtual worker with visual impairment and the experiential factors, with special attention to inaccessible technology, that shape the unique standpoint of the virtual worker who has visual impairment.Implications for practitioners: Both theoretical and applied implications are presented. This study takes note of the social factors that surround the navigation of the workplace with a focus on how communicating about access, advocating for accessibility, and requesting assistive technology are embedded in a larger conversation of culture and societal norms of employment. Accessibility is discussed as both a technical and social challenge. This consideration of accessibility is crucial in current and future workplaces where even the simplest task is to be completed via a technological tool.